Immunogenicity, Tolerability, and Clinical Effectiveness of 23-Valent Polysaccharide Pneumococcal Vaccine in Patients with Systemic Lupus Erythematosus - G. M. Tarasova; B. S. Belov; M. V. Cherkasova; S. K. Soloviev; E. A. Aseeva; T. M. Reshetnyak; T. V. Popkova; N. M. Kosheleva (Антибиотики и Химиотерапия)
The aim of the work is to study the immunogenicity, tolerability, and clinical efficacy of the 23-valent polysaccharide pneumococcal vaccine (PPV-23) in patients with systemic lupus erythematosus (SLE). Material and methods. The study included 61 patients with a confirmed diagnosis of SLE, including 53 women, 8 men, aged 19 to 68 years. The disease activity at the time of vaccination: in 9 patients — high, in 13 — medium, in 34 — low, in 5 — remission. Therapy outline: 59 patients received glucocorticoids (GC) 5–30 mg/day in terms of prednisolone, 45 — hydroxychloroquine (GC), 33 — cytostatics (CS), 22 — genetically engineered biological drugs (GEBD): 11 — rituximab (RTM), 10 — belimumab (BLM). 23-valent polysaccharide pneumococcal vaccine in an amount of 0.5 ml (1 dose) was injected subcutaneously. Follow-up period: 9 patients — 3 months, 52 — 1 year after the vaccination. Patients were examined before vaccination, as well as in 1, 3, and 12 months after the vaccination. Results and discussion. After a year of observation, the number of «responders» to vaccination was 61.5%, «non-responders» — 38.5%. There was a decreased response to vaccine in patients receiving GEBD compared with patients who did not receive GEBD (40% and 75%, respectively), p=0.02. No differences were found against the background of RTM and BLM therapy. Administering GC in a dose exceeding 10 mg/day did not lead to a more significant decrease in response to vaccine compared to other patients. Standard local vaccination reactions of mild to moderate severity were noted in 50.8% of the patients, general reaction of mild severity — in 1 patient (1.6%), hyperergic Arthus-like reaction — in 1 patient (1.6%), the symptoms of which were relieved in 7 days. During the observation period (1 year), not a single case of exacerbation of SLE, reliably associated with the vaccination, was registered, and no new autoimmune phenomena were identified. Clinically positive dynamics was noted in the form of a decrease in the number of episodes of pneumonia, as well as acute and exacerbated chronic bronchitis, sinusitis. Conclusion. Sufficient immunogenicity, good tolerance, and clinical effectiveness of PPV-23 in patients with SLE, incl. those, who received combined immunosuppressive therapy. Further studies are needed in large groups of patients with long follow-up periods.